Probabilistic behavior of DNA segregation in Escherichia coli. - Cooper, S (1978)
The pattern of segregation of DNA in Escherichia coli B/rK was analyzed by using the Methocel technique for forming chains of cells and the membrane binding elution method. Strain B/rK was shown to have a relatively high degree of nonrandom segregation and was used in a critical experiment to test the proposal that only one DNA strand acts nonrandomly during segregation. Thymidine-labeled cells were bound to a nitrocellulose membrane, and newly dividing cells were eluted from the membrane for six generations. The segregation of DNA in the eluted cells as well as in the cells bound to the membrane was examined by the Methocel technique. No difference in segregation was found between the two populations of cells, a result which indicates that the two strands are equivalent in segregation and that the pattern of segregation is not the result of a permanent binding of any strand to a pole of a cell.